Day 3 Wed, April 18, 2018 2018
DOI: 10.2118/190489-ms
|View full text |Cite
|
Sign up to set email alerts
|

Waste Water Treatment by Chemical Coagulation Method-Increasing Output and Reducing Environmental Impact

Abstract: Cairn, Oil & Gas vertical of Vedanta Limited operates ~27 per cent of India’s domestic crude oil production processing upto 1MM bbls of produced fluid. Management and disposal of produced water after stimulation and work over/completion is one of the most challenging problems to sustain productivity without upsetting the surface facility. In order to prevent facility upset, the initial flow back of spent acid is taken into lined pit to allow for longer residence time and effective separation before treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Dastgheib et al [62] have verified coagulants like ferric chloride (FeCl 3 ) and aluminum sulphate (Al 2 (SO 4 ) 3 ) by jar tests. Agarwal et al [63] found poly aluminium chloride (PAC) to be suitable coagulant for flowback fluid. Hosny et al [64] proved that chitosan from shrimp shells mixed with carboxy methyl cellulose as a coagulant allow to remove 99% of oil from oily produced water.…”
Section: Selection Of the Optimal Dose Of Coagulantmentioning
confidence: 99%
“…Dastgheib et al [62] have verified coagulants like ferric chloride (FeCl 3 ) and aluminum sulphate (Al 2 (SO 4 ) 3 ) by jar tests. Agarwal et al [63] found poly aluminium chloride (PAC) to be suitable coagulant for flowback fluid. Hosny et al [64] proved that chitosan from shrimp shells mixed with carboxy methyl cellulose as a coagulant allow to remove 99% of oil from oily produced water.…”
Section: Selection Of the Optimal Dose Of Coagulantmentioning
confidence: 99%